Potential of Cameroon-indigenous isolates of the entomopathogenic fungi Beauveria bassiana and Metarhizium anisopliae as microbial control agents of the flea beetle Nisotra uniformis - Niyibizi, I.A.B.; Hanna, R.; Kekeunou, S.; Membang, G.; Fiaboe, K.; Mahot, H.C.; Abang, A.F.; Kumar, P. Lava; Fotso Kuate, A. (Informa UK Limited, 2023)
The flea beetle Nisotra uniformis Jacoby is a widespread pest of malvaceous crops for which synthetic chemical insecticides remain the principal control tool, particularly in sub-Saharan Africa. With the ultimate aim of developing a microbial alternative for N. uniformis control, we conducted laboratory experiments (25 ± 1°C; 70 - 80% RH) to evaluate the biological attributes of three Cameroonian isolates of the entomopathogenic fungi Beauveria bassiana (Balsamo-Crivelli) Vuillemin and Metarhizium anisopliae sensu lato (Metchnikoff) Sorokin. Spore germination rates of the isolates varied from 0.5% after 4 hrs to 100% after 24 hrs on PDA medium, with MIITAC11.3.4 spores germinating fastest. Pathogenicity tests consisted of dipping adult beetles in conidial suspensions. All isolates were pathogenic to N. uniformis, with corrected mortalities varying between 23.3 - 86.7%. BIITAC-O-2 had the lowest LC50 at 5.17 × 106 conidia/ml, while MIITAC11.3.4 and BIITAC6.2.2 had LC50 at 4.11 × 107 conidia/ml, and 2.00 × 108 conidia/ml, respectively. BIITAC6.2.2 produced the shortest time to the highest mortality rate (1.17 days) and the shortest LT50 of 1.64 days but only at the highest concentration, followed by the two highest concentrations of MIITAC11.3.4 (LT50 at 3.43 and 5.70 days). The c parameter in the Weibull model showed that BIITAC-O-2 caused the highest rate of increase in mortality (2.42) at the highest concentration, followed by MIITAC11.3.4 (1.09) and BIITAC6.2.2 (0.50). The results of our study provide the basis for including N. uniformis in the ongoing development of BIITAC6.2.2 and MIITAC11.3.4 into biopesticide while continuing with further laboratory studies on BIITAC-O-2.